A Platelet Graphitic Nanofiber‐Carbon Nanotube Hybrid for Efficient Oxygen Evolution Reaction - Ali, Zulfiqar; Mehmood, Mazhar; Ahmad, Jamil; Li, Xin; Majeed, Abdul; Tabassum, Hassina; Hou, Peng‐Xiang; Liu, Chang (ChemCatChem, 2020)
Carbon nanostructures with a high‐density of active sites are needed as catalysts for the oxygen evolution reaction (OER). Here we report a platelet graphitic nanofiber‐carbon nanotube (PGNF‐CNT) hybrid electrocatalyst prepared by chemical vapor deposition. The material is composed of interconnected CNTs and nanofibers consisting of graphitized carbon layers stacked at different angles to the fiber axis with a large number of exposed edges. These unique structural characteristics give the hybrid a high density of active sites, fast electron transfer and a large number of mass transport paths. As a result, the material has an excellent electrocatalytic activity for OER with an overpotential of 0.28 V at a current density of 10 mA cm−2, which is much better than those of Ir/C and previously‐reported carbonaceous catalysts. OER catalysis: A platelet graphitic nanofiber‐carbon nanotube (PGNF‐CNT) hybrid for OER catalysis, the PGNF composed of stacked carbon flakes with numerous exposed edges provides sufficient active sites, while CNTs function as a pathway permitting fast electron transport.